Effect of Melinjo (Gnetum gnemon L) Peel Flour Fortification on the Quality of Tuna Crackers - Humaira, Yara; zarwinda, irma; Elfariyanti, Elfariyanti (Universitas Serambi Mekkah, 2025)
This study aimed to determine the effect of melinjo (Gnetum gnemon L.) peel flour fortification on the chemical and sensory quality of tuna fish (Euthynnus affinis, locally known as tongkol) crackers. The research was conducted using an experimental laboratory design with four formulations: F0 (without melinjo peel flour), F1 (5 g), F2 (10 g), and F3 (15 g). The parameters observed included sensory evaluation (color, aroma, taste, texture, and crispness) and chemical analysis consisting of moisture content, acid-insoluble ash, and protein content, in accordance with the Indonesian National Standard (SNI 8272:2016). The results showed that the addition of melinjo peel flour significantly affected the protein content of tuna fish crackers. Protein levels increased from 7.8% in F0 to 13.3% in F3, while moisture content decreased from 6.91% to 5.72%. Acid-insoluble ash values ranged from 0.08% to 0.17%, and all samples met the SNI quality standard of less than 0.20%. Sensory evaluation indicated that adding 10–15 g of melinjo peel flour produced the highest acceptance scores, characterized by a natural brownish color, distinctive aroma, and crisp texture.These findings demonstrate that melinjo peel flour can be effectively used as a natural fortifying ingredient to enhance the protein content and sensory quality of tuna fish crackers without reducing consumer acceptance. This fortification approach also supports the development of healthy, economical, and sustainable functional foods based on local resources.